Investigating the role of starch in the structuring of meat alternatives from mung bean and pea protein isolates via heat-induced gelation - Baig, Mohammad Affan; Mostafa, Hussein; Sivapragasam, Nilushni; Aslam, Raouf; Zhou, Weibiao; Maqsood, Sajid (Frontiers in Sustainable Food Systems, 2024)
Introduction The structuring of plant-based meat alternatives is a complex process which is highly dependent on qualitative and quantitative proportion of different ingredients. In the present study, starch, protein, and oil concentrations were optimized for the formulation of meat alternative (MA) using response surface methodology (RSM). Methods Protein isolates of mung bean and pea protein, & corn starch were used along with sunflower oil to formulate meat alternatives using heat-induced gelation. The protein functionality of mungbean protein isolate (MBPI) and pea protein isolate (PPI) were analyzed. In addition, the effects of constituent composition on the physicochemical properties of meat alternatives were studied using RSM. Results The protein content exhibited an elevation with increased levels of MBPI and PPI in 15:15 ratio. Moisture and hardness were chiefly influenced by oil content, as they displayed a decline with increasing oil levels. The color (L*) was principally affected by starch and oil, where the L* reduced with increasing levels of both variables. Springiness was influenced by the interaction of protein ratio (MBPI:PPI) and starch, as it showed a lowest value at the lowest level of protein and the highest level of starch. Chewiness was influenced by the interaction of hardness and springiness. The microstructure analysis showed dense protein matrix in the meat alternative. Discussion Overall, the study shows that starch facilitated the structuring of meat alternative formulated using MBPI and PPI which could be utilized as potential materials for enhanced textural properties of the meat alternatives.